The Influence of Learning Cycle 9E Viewed from Computational Thinking Theory to Scientific Literacy Skills, Critical Thinking Skills, and Creativity - Toni Efriyandika; Resna Hegi Putra; Yuni Pantiwati; Iin Hindun; Abdulkadir Rahardjanto (WISE Pendidikan Indonesia, 2025)
The main challenge in biology learning lies in students’ low levels of scientific literacy, critical thinking, and creativity, often caused by teacher-centered practices that limit exploration and reflection. This study investigates the effect of the 9E Learning Cycle model integrated with Computational Thinking (CT) on improving students’ scientific literacy, critical thinking, and creativity. A quasi-experimental design was used with three groups—experimental, positive control, and negative control—at MAN 1 West Lampung. Data were collected through pretests, posttests, and observations, analyzed using N-Gain and t-tests. The results show significant improvement in the experimental class, with science literacy increasing from 42% to 87% (N-Gain = 0.78, high category), critical thinking from 55% to 77%, and creativity from 51% to 79%. These findings indicate that the 9E Learning Cycle effectively enhances conceptual understanding, analytical reasoning, and creative problem-solving. The study concludes that integrating computational thinking within the 9E framework promotes 21st-century skills and supports the achievement of sustainable quality education in science learning.